2013
DOI: 10.1002/mbo3.119
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Deinococcus‐Thermus molecular diversity by novel group‐specific PCR primers

Abstract: The deeply branching Deinococcus-Thermus lineage is recognized as one of the most extremophilic phylum of bacteria. In previous studies, the presence of Deinococcus-related bacteria in the hot arid Tunisian desert of Tataouine was demonstrated through combined molecular and culture-based approaches. Similarly, Thermus-related bacteria have been detected in Tunisian geothermal springs. The present work was conducted to explore the molecular diversity within the Deinococcus-Thermus phylum in these extreme enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 65 publications
(97 reference statements)
2
20
0
3
Order By: Relevance
“…Deinococcus–Thermus spp. are usually found in extreme environments ( Theodorakopoulos et al, 2013 ). They have also been detected in the feces of some animals with only a few clones ( Lagier et al, 2012 ; McLaughlin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deinococcus–Thermus spp. are usually found in extreme environments ( Theodorakopoulos et al, 2013 ). They have also been detected in the feces of some animals with only a few clones ( Lagier et al, 2012 ; McLaughlin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mortazavi et al ( 2013 ) reported the presence of Deinococus-Thermus (1%) in the intertidal sediments of the Gulf of Mexico. Deinococcus-Thermus is composed primarily of bacteria that are resistant to environmental hazards such as ultraviolet and ionizing radiations, oxidizing agents, dessicating conditions, and high temperatures (Henne et al, 2004 ; Cox and Battista, 2005 ; Omelchenko et al, 2005 ; Theodorakopoulos et al, 2013 ). Thus, strong solar radiation and perhaps high temperature (28–30°C), are main drivers of the dominance of these bacteria in late stages of irradiated dispersant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on transcript level TRFLP analysis, Deinococcus - Thermus related microbes, Proteobacteria as well as Actinobacteria were active in Schlöppnerbrunnen fen under variable environmental conditions. Deinococcus - Thermus related microbes represent a deep-branching group that are widespread in extreme environments and resistant to environmental stress (da Costa et al, 2006 ; Theodorakopoulos et al, 2013 ). Proteobacteria are found in most soil ecosystems and under a variety of environmental conditions due to their versatile metabolic capabilities (Dworkin et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%